A unique species of Triantha (Tofieldiaceae) endemic to New Jersey, U.S.A. deserves a name - Eisenman, Sasha W. (Phytotaxa, 2026)
The genus Triantha (Tofieldiaceae) consists of four species, two of which, Triantha glutinosa and Triantha racemosa, have populations that are found in eastern North America. T. glutinosa has a primary distribution across Canada and into the northern United States, and is found in marshes, wet meadows, and on calcareous soil. T. racemosa primarily occurs on the Gulf Coast and in the southeastern United States in boggy areas, pine barrens, and savannas with acidic soils. The distribution of T. racemosa has never been known to extend beyond southern New Jersey. In the past, populations of Triantha found in New Jersey were identified as Triantha racemosa, though these plants have also been noted to exhibit some morphological characteristics associated with T. glutinosa. It has previously been hypothesized that the New Jersey populations are actually hybrids of T. glutinosa and T. racemosa, and that the two species may have had overlapping ranges at some point in the past. New Jersey populations are currently isolated from the nearest T. glutinosa and T. racemosa localities by hundreds of miles, too distant for gene flow to occur. Sequence analyses of the trnH-psbA intergenic spacer and matK gene region of chloroplast DNA (cpDNA), and the internal transcribed spacer (ITS) of nuclear ribosomal DNA and PCR-RFLP confirm the unique genetic identity of New Jersey populations of Triantha. Due to their unique genetic sequences, unique morphology, and a distribution that is isolated from extant T. glutinosa and T. racemosa populations, a new nothospecies, Triantha × novacaesariensis, is described for New Jersey populations of Triantha.